2020
DOI: 10.1016/j.celrep.2020.03.035
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Modulate CD8 T Cell Responses to Influence Colitis-Associated Tumorigenesis

Abstract: Highlights d Dysbiosis can lead to increased colon tumor susceptibility and CD8 + IFNg + T cells d Increased colon CD8 + IFNg + T cells are associated with more inflammation and tumors d Dysbiosis and increased tumorigenesis are associated with greater T cell exhaustion

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
79
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(79 citation statements)
references
References 92 publications
0
79
0
Order By: Relevance
“…Indeed, gnotobiotic mice colonized with a Helicobacter -dominated microbiota from wild mice are partially protected from CRC induced by AOM-DSS (Rosshart et al, 2017). Conversely, some laboratory microbiomes containing other Helicobacter strains decrease the effectiveness of CD8 + T cell control over colorectal tumors (Yu et al, 2020), so it will be important to tease out the specific mechanisms employed by different strains of Helicobacter to induce mucosal immune responses. In humans, colonization with Helicobacter pylori has plummeted 2-3 fold over the past few decades with the lowest rates of infection being seen in young people (Jiang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, gnotobiotic mice colonized with a Helicobacter -dominated microbiota from wild mice are partially protected from CRC induced by AOM-DSS (Rosshart et al, 2017). Conversely, some laboratory microbiomes containing other Helicobacter strains decrease the effectiveness of CD8 + T cell control over colorectal tumors (Yu et al, 2020), so it will be important to tease out the specific mechanisms employed by different strains of Helicobacter to induce mucosal immune responses. In humans, colonization with Helicobacter pylori has plummeted 2-3 fold over the past few decades with the lowest rates of infection being seen in young people (Jiang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact mechanisms remain to be discovered, a growing number of preclinical animal model studies and clinical trials of immunotherapies suggest that the host microbiome is a critical determinant for the variable host responses to different therapy modalities [18]. Yu et al demonstrated that the same type of pro-inflammatory cells induced due to dysbiosis leads to increased T cell exhaustion in the tumor microenvironment [19]. Gut microbiota dysbiosis also increases the intestinal barrier's permeability, favoring bacterial translocation, macrophages activation, and the consequent establishment of chronic pro-tumorigenic inflammation.…”
Section: Microbiome Local and Systemic Immune Responses And Cancermentioning
confidence: 99%
“…58 When considering how these mechanisms may link to the gut microbiota, it is known that gut microbiota are key regulators of CD8+ T cell function. 59 The gut microbiota that produce SCFA can promote the memory potential of antigen-activated CD8+T cells. 60 In terms of mounting a response directly against the SARS-CoV-2 virus, it has been demonstrated that the SCFAs, butyrate and, to a lesser extent, propionate directly modulate gene expression of CD8+ cytotoxic T lymphocytes (CTLs) and Tc17 cells.…”
Section: Microbiome-immune Interactionsmentioning
confidence: 99%